Association between FOXE1 and non-syndromic orofacial clefts in a northeastern Chinese population. Issue 8 (October 2015) - Liu, Kun; Lu, Yongping; Ai, Lisi; Jiao, Boqiang; Yu, Jiantao; Zhang, Bin; Liu, Qiang
Abstract Non-syndromic orofacial clefts are among the most common congenital defects, and several reports have shown that the FOXE1 gene has strong associations with them. To find out if the gene was a risk factor we used a case–control and family-based analysis, and recruited 230 patients with non-syndromic oral clefts including 179 with non-syndromic cleft lip with or without cleft palate, and 51 with non-syndromic cleft palate alone, their parents (166 mothers and 161 fathers, including 135 complete trios), and 180 healthy controls. Polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) were used to genotype the 2 most strongly associated markers (rs4460498 and rs3758249) in FOXE1, and case–control and family-based associations were analysed. In the case-control analyses we found a significant association with non-syndromic cleft lip and palate in rs4460498 (p=0.009) and rs3758249 (p=0.014), but no association in patients with cleft palate alone. For rs4460498 in FOXE1, the odds ratio (OR) for cases with CC homozygotes compared with TC+CC genotypes was 1.813 (95% CI 1.176 to 2.796), and for rs3758249 in FOXE1, the OR for cases with GG homozygotes compared with those with AG+AA genotypes was 0.561 (95%CI 0.371 to 0.848). The results of transmission-disequilibrium tests for rs4460698 and rs3758249 for non-syndromic orofacial clefts were p=0.003, OR=2.781 (95% CI 1.414 to 5.469) and p=0.001, OR=2.552 (95%CI 1.574 to 4.138), respectively. This suggests that FOXE1 (rs4460498 and rs3758249) is strongly associated with non-syndromic cleft lip and palate in populations in northeast China, and further study between FOXE1 and non-syndromic orofacial clefts is necessary.